ARCHITECTURE TOOLS MEASURE THE LEVELS OF SALT AND PH OF SEAWATER USING A FUZZY LOGIC-BASED ANDROID - Achmad Ubaidillah; Diana Rahmawati; Rocky Aiman (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
The sea has many potentials to be utilized based on the ecological aspects of coastal area. Almost in the coastal areas and islands in Madura are experiencing difficulties in utilizing marine resources. Salinity changes influenced by water osmotic pressure whereas biota living in salt water should be able to adjust the osmotic pressure from its environment. The changes in pH have an effect on the survival of marine organisms as not all saltwater creatures survive with the change of it. From these problems a system of "Designing Measure of Salt Measure and Sea Water pH Using Fuzzy Logic Based Android" is made. Where measuring system is made to prioritize the level of accuracy of changes in salinity and pH value of sea water. So that people could exploit the sea potential based on the condition of the sea water. The reading of sea water condition changes using salinity sensors, pH sensors, and MCU nodes as communication with android devices. Input from the sensor can be sent to the web server and received by android and then processed by fuzzy logic method to get the maximum output. The system can work according to what is expected during 5 days of testing in different locations. The success of this system is 97.3% with a 2.07% failure rate.DOI : https://doi.org/10.26905/jeemecs.v1i2.2662